Indicative performance competencies for social workers in the Sultanate's schools: principals and social supervisors’ perspectives = الكفايات الإرشادية الأدائية للأخصائيين الاجتماعيين بمدارس السلطنة: دراسة من وجهة نظر مدراء المدارس والمشرفين الاجتماعيين - Khalafan, Alshuaili Moosa Suliaman; Abd. Hamid, Siti Rafiah (International Organization Center of Academic Research (OCERINT), 2020)
This quantitative study discussed the indicative efficiencies of social workers in the Sultanate’s schools. The problem was: studies conducted on social workers in the school indicated that; they need more training in vocational competencies. They complain of poor qualification, their need for indicative performance competencies. The objective of the study; to diagnose the indicative performance competencies for social workers, and to detect any statistically significant differences in the average of specialists' ability according to the variables. A random sample was chosen from Muscat Governorate, Al Dakhiliyah Region, and South Al Batinah Region, amounting to (312) social education directors and supervisors. A questionnaire was developed consisting of (68) items distributed in (7) fields. Descriptive analysis and mono-variance analysis were adopted. The findings showed that: the social workers possess a high degree in the field of personal characteristics in the first place, communication and external relations, then the field of collective guidance, then the field of documentation and registration. It was a moderate degree in the areas of: individual counseling and skills, then the scope of the guiding plan, and finally the field of group counseling. The results also indicated that there are statistically significant differences for the gender variable in favor of females in the performance of guiding performance competencies, as well as for the qualification variable and in favor of a bachelor's degree, and the educational district in favor of the Governorate of Muscat, and in favor of school administrators. ******************************************************************************** ناقشت هذه الدراسة الكمية الكفايات الإرشادية الأدائية للأخصائيين الاجتماعيين بمدارس السلطنة. برزت المشكلة: أنَّ كثير من الدراسات التي أجريت على الأخصائيين الاجتماعيين في المجال المدرسي، أشارت إلى أنهم بحاجة إلى مزيد من التدريب على الكفايات المهنية، وخاصة ما يتعلق منها بالجانب الإرشادي. وهم يشتكون من ضعف تأهيلهم، وحاجتهم إلى كفايات أدائية إرشادية. لذا هدفت الدراسة: تشخيص مستوى درجة الكفايات الإرشادية الأدائية لدى الأخصائيين الاجتماعيين، والكشف عن أية فروق دالة إحصائية في متوسط تمكن الأخصائيين تبعا للمتغيرات. تم اختيار عينة عشوائية من محافظة مسقط، والمنطقة الداخلية، ومنطقة جنوب الباطنة، بلغت (312) مديرا ومشرفا للتربية الاجتماعية. وتم تطوير استبانة مكونة من (68) فقرة موزعة في (7) مجالات. اعتمد التحليل الوصفي، وتحليل التباين الأحادي. أظهرت النتائج: أن الأخصائيين الاجتماعيين يمتلكون درجة عالية في مجال السمات الشخصية في المرتبة الأولى، والاتصال والعلاقات الخارجية، ثم مجال التوجيه الجمعي، ثم مجال التوثيق والتسجيل. وكانت بدرجة متوسطة في مجالات: الإرشاد الفردي ومهاراته، ثم مجال الخطة الإرشادية، وأخيرا مجال الإرشاد الجمعي. كما أشارت النتائج إلى وجود فروق دالة إحصائيا لمتغير الجنس لصالح الإناث في امتلاك الكفايات الإرشادية الأدائية، كذلك لمتغير المؤهل ولصالح حملة درجة البكالوريوس، وللمنطقة التعليمية لصالح محافظة مسقط، ولصالح مدراء المدارس.